Ammonia production from nitrogen and hydrogen supplied via pipeline using iron catalyst a plant design - Bukuhan, Kirsten Duane M.; Dimabuyu, Froilan F.; Morales, Chechen A.; Agutaya, Jonas Karl Christopher N. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
While ammonia finds extensive use in such processes as explosives production and refrigeration, its main application is in the manufacture of fertilizer. Agricultural countries, such as the Philippines, rely heavily on ammonia and its derivatives like urea for the production of fertilizers. However, there is currently no local production of ammonia in the Philippines, thus resulting in heavy ammonia importation. This study focused on the technical and economical feasibility of a Philippine-based ammonia production plant sourcing its raw materials via pipeline. Based on the import of ammonia, the capacity of the plant was set to 111,846 MT on ammonia per year. With this capacity and the prices of both the raw materials and the product, the economic potential yielded a value of USD 433.01/MT of NH3. Preliminary studies were done in order to determine the key unit operations and processes needed to operate the plant, along with the initial feasibility of the plant. A nearby air separation facility was selected to supply the nitrogen and hydrogen requirements of the plant. Recycle and purge system were found to be crucial in the process as with conventional ammonia plants. The process itself is greatly simplified relative to conventional ammonia plants due to the direct sourcing of both the raw materials. It can be divided into three sections. The first section is the compression section, where the raw materials are sent to a series of compressors in order to reach the pressure required by the reactor. The second is the conversion or synthesis section where the compressed gases are mixed with a recycle stream, preheated using a heat exchanger and a heater in series, then partially converted to ammonia using two fixed-bed reactors. The third is the separation section in which the gaseous ammonia is condensed in a condenser in order to separate it from the non condensable nitrogen and hydrogen.
Submitted in partial fulfillment of the requirements in ChE 142 Chemical Engineering Plant Design.
Keywords: Ammonia; Chemical plants -- Design and construction